An efficient protocol for the preparation of linear arabino-oligosaccharides. (October 2020) - Shi, Huimin; Xu, Jialei; Wang, Wenqing; Jia, Mengdi; Zhou, Yifa; Sun, Lin
Abstract: In this study, we report the development of an efficient protocol in the preparation of linear arabino-oligosaccharides derived from sugar beet arabinan. By optimizing hydrolytic conditions and separation on tandem Bio-Gel P4 columns, we obtained arabino-oligosaccharides with various degrees of polymerization (DP) from 2 to 15. All of these α-1, 5-linked arabino-oligosaccharides are highly pure (>95%) as determined by HPAEC, MALDI-TOF mass spectrometry and 13 C NMR spectroscopy. Due to their purity, these oligosaccharides can be used as standards to identify other oligosaccharides and as substrates to characterize new arabinan-specific enzymes, as well as for the development of new functional oligosaccharides. Graphical abstract: Image 1 Highlights: An efficient protocol was developed to prepare linear arabino-oligosaccharides. A series of arabino-oligosaccharides with DP 2 to 15 were produced. They were characterized by HPAEC, MALDI-TOF MS and 13 C NMR spectroscopy. These oligosaccharides were all in the form of α-1, 5-linkages with high purity.